ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DI MASA PANDEMI COVID-19 PADA MATERI HUKUM DASAR KIMIA DI PPM MA AL-IZZAH AL-AS'ADIYAH TOLAI - Muh Junaidi; Minarni Rama Jura; Kasmudin Mustapa; Sri Hastuti Virgianti Pulukadang (Universitas Tadulako, 2022)
This study aims to analyze students' creative thinking skills during the covid-19 pandemic on basic chemical law material at PPM MA Al-Izzah Al-As'adiyah Tolai. The subjects of this study were 24 people with 11 male students and 13 female students representing all students of class X IPA PPM MA Al-Izzah Al-As'adiyah Tolai. The data collection instrument was an essay test in the form of a description of students' creative thinking skills on the basic legal material of chemistry as many as 8 questions. Based on the results of research and data analysis, the percentage of fluency indicators is 69.79% in the quite creative category, the flexibility indicator is 55.56% in the creative enough category, and the originality indicator is 71.35% in the original category. creative, and the elaboration indicator is 53.64% in the less creative category. Based on the four indicators of creative thinking ability showing the creative thinking ability of students of class X IPA PPM MA Al-Izzah Al-As'adiyah Tolai, the percentage of 62.59% is in the quite creative category. So that it can be categorized as MA Al-Izzah Al-As'adiyah Tolai students who are quite creative.